Sensitivity to halothane and its relationship to the development of PSE (Pale, Soft, Exudative) meat in female lineage broilers - Marchi,Denis Fabrício (2009)
This work aimed to evaluate female lineage broilers for halothane sensitivity and for their susceptibility to the subsequent development of PSE meat. The halothane test was carried out in an anesthetic chamber with 3.0% halothane. The unconscious birds were examined for leg muscle rigidity. If one or both legs became extended and rigid, the birds were classified as halothane sensitive (HAL+), while unresponsive birds were classified as halothane negative (HAL-). The results showed that of 298 birds aged 42 days old, 95.6% were HAL- and 4.4% were HAL+. A sample of pectoralis major muscle was collected from HAL- (n=105) and HAL+ (n=13) birds. The pH and breast fillet color were determined at 4ºC, 24 hours post-mortem. Interestingly, only 2.5% of HAL+ birds displayed PSE meat characteristics compared to 12.7% of HAL- individuals. The halothane test demonstrated that female lineage broilers displayed very little sensitivity towards halothane, indicating that the development of PSE meat is related to other environmental factors.